Microservices Are the New Building Blocks of Financial Technology. Issue 87 (January 2017) - Adler, Marc
Abstract : Due to an error, the November 2016 Cover story listed the incorrect author for the Quantifi article. This Erratum corrects the authorship of this article, which was written by Marc Adler.